Q&A. (1st August 2019) - Watts, Sarah
Abstract : Sarah Watts is a music educator, musician and composer. She is most well known for her highly successful educational book series that emphasises the playful side of music-making. Her most famous works include Red Hot Recorder, Razzamajazz, and the Five Note Philharmonic